On the Oosterhoff dichotomy in the Galactic bulge: I. spatial distribution - Prudil, Zdeněk; Dékány, István; Grebel, Eva K. (Monthly notices of the Royal Astronomical Society, 2019)
Abstract. We present a study of the Oosterhoff (Oo) dichotomy in the Galactic bulge using 8141 fundamental-mode RR Lyrae stars. We used public photometric data
Gesehen am 18.02.2019